The New Deal as a Triumph of Social Work - Miller, S. author. aut Link
VIII, 162 p.
Keywords: The New Deal as a Triumph of Social Work concerns the 'hand' the New Deal plays from the perspective of early American History in which government and business cooperation is assumed and economic rights are addressed collectively whereas political rights are considered individually. The New Deal reconfigures this 'ratio' of rights by folding 'social work' into the aims of government. Miller describes the vital part Frances Perkins and her personal history play in this development.